Deposição de filmes de tio2 usando plasma em gaiola catódica - Morais, Priscila Borges de (Universidade Federal Rural do Semi-Árido, 2017)
Titanium oxides are well studied due to their importance in tribo-mechanical, biomedical, optical and electronic applications. Research into new technologies that increase and / or reduce costs are constantly being sought. In the present work, an alternative film deposition technique, called cathodic discharge plasma (PDGC), was used to study the influence of the process parameters on the characteristics of the film. Glass was used as the substrate. The deposition process was carried out in a reactor, maintaining fixed pressure and temperature. Different concentrations of the Ar-O2 mixture were used for the plasma atmosphere and deposition times ranging from 1h-8h. The obtained films were characterized for wettability, crystalline phases, microstructure, transmittance and optical absorbance. It was verified that there was the formation of titanium dioxide in all the samples, with predominance of the rutile structure. The thickness of the films increased proportionally to the time of deposition and oxygen flow, with deposition rate between 1,93 and 6,07 nm/min. The cathodic cushion deposition process was found to be effective and under these conditions produced TiO2 films with properties that can be applied to self-cleaning and photocatalytic surfaces
Keywords: Gaiola-Catódica; Plasma; Filmes Finos; Anatase; Rutilo; Cathodic Cage; Plasma; Thin Films; Anatase; Rutile; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA